2018
DOI: 10.3390/diseases6010019
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-Uricemia and Gouty Access in the Adult Population of the Southeast of Gabon: Biochemical Aspects

Abstract: Gout is caused by a chronic hyperuricemia whose complications are not currently well evaluated in Africa. The aim of this study was to determine the prevalence and risk factors of hyperuricemia and gout in 85 patients recruited. A total of 26 cases of hyperuricemia, i.e., 30.6% of the study population, with 12 cases of gout and seven cases of gouty access. In this population, hyperuricemia was proportional to age (p-value < 10−4, OR = 2.6), but it was more prevalent in men, 23.5% versus 7.1% for women (p-value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…However, these studies suggest that while the trends and the patterns of gout remain similar to other populations, the incidence and prevalence of HU and gout is low [ 34 , 35 ]. Furthermore, a study found that the prevalence of gout was 14.1% among 85 African patients in Southeast Gabon ( Table 5 ) [ 36 ]. This prevalence of gout was likely high due to the study’s inclusion criteria of participants who were requesting urate level tests, leading to a biased and underrepresented sample of the African population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these studies suggest that while the trends and the patterns of gout remain similar to other populations, the incidence and prevalence of HU and gout is low [ 34 , 35 ]. Furthermore, a study found that the prevalence of gout was 14.1% among 85 African patients in Southeast Gabon ( Table 5 ) [ 36 ]. This prevalence of gout was likely high due to the study’s inclusion criteria of participants who were requesting urate level tests, leading to a biased and underrepresented sample of the African population.…”
Section: Resultsmentioning
confidence: 99%
“… a Based on HU prevalence in adult men and women within Irish Health System [ 38 ] and Italian Primary Care database in 2009 [ 39 ], gout prevalence data derived from Germany, Italy, France, Portugal, UK, and Greece [ 30 ]. b Based on a study population of 85 African men and women conducted in Southeast Gabon [ 36 ]. c Based on the Shandong coastal cities of Eastern Chinese [ 40 ] and systematic review of HU in mainland China [ 40 , 41 ].…”
Section: Tablementioning
confidence: 99%
“…(30,31) Furthermore, a study found that the prevalence of gout was 14.1% among 85 African patients in Southeast Gabon (Table 5). (32) This prevalence of gout was likely high due to the study's inclusion criteria of participants who were requesting urate level tests, leading to a biased and underrepresented sample of the African population. Another cross-sectional study prescribed anti-gout medications to 4.0% in 400 African patient enrollees seeking treatment for joint pain in Madagascar.…”
Section: Epidemiology Of Hyperuricemia and Goutmentioning
confidence: 99%
“…В большинстве популяций гиперурикемия больше распространена среди мужчин, чем среди женщин. Так, в российской популяции гиперурикемия почти в 2 раза чаще встречается среди мужчин (25,3% против 11,3%) [35], в Корее, Китае и юго-восточной Африке также превалирует мужской тренд распространенности гиперурикемии [36][37][38]. Гиперурикемия положительно ассоциируется с возрастом, ожирением, метаболическим синдромом, почечной недостаточностью и субклиническим воспалением у обоих полов, в то время как потребление алкоголя, образование и текущий статус курения имели положительную связь с гиперурикемией только у женщин [36].…”
Section: традиционные факторы ссрunclassified